2014
DOI: 10.3382/ps.2014-04200
|View full text |Cite
|
Sign up to set email alerts
|

Feed supplementation with red seaweeds, Chondrus crispus and Sarcodiotheca gaudichaudii, affects performance, egg quality, and gut microbiota of layer hens

Abstract: The aim of this study was to evaluate the effect of the inclusion of red seaweed supplementation to standard poultry diets on production performance, egg quality, intestinal histology, and cecal short-chain fatty acids in Lohmann Brown Classic laying hens. A total of 160 birds were randomly assigned to 8 treatment groups. Control hens were fed a basal layer diet; positive control hens were fed a diet containing 2% inulin; and 6 treatment groups were fed a diet containing one of the following; 0.5, 1, or 2% Cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 68 publications
9
119
1
2
Order By: Relevance
“…Interestingly in the present study, a negative correlation was observed between the relative abundance of Lactobacillus acidophilus and Salmonella Enteritidis in the birds supplemented with CC (4%) ( Figure 3 ), suggesting Lactobacillus acidophilus as a suppressor of Salmonella Enteritidis (Gibson et al, 2005). Moreover, this could be due to the effect of dietary C. crispus on the epithelial cell turnover, thus altering the growth in favor of the beneficial bacteria (Kulshreshtha et al, 2014). Previously, it has been documented that the host microbiota composition is dependent on the dietary carbohydrate intake (Rinttilä and Apajalahti, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly in the present study, a negative correlation was observed between the relative abundance of Lactobacillus acidophilus and Salmonella Enteritidis in the birds supplemented with CC (4%) ( Figure 3 ), suggesting Lactobacillus acidophilus as a suppressor of Salmonella Enteritidis (Gibson et al, 2005). Moreover, this could be due to the effect of dietary C. crispus on the epithelial cell turnover, thus altering the growth in favor of the beneficial bacteria (Kulshreshtha et al, 2014). Previously, it has been documented that the host microbiota composition is dependent on the dietary carbohydrate intake (Rinttilä and Apajalahti, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The population of microbes within the gut was determined by quantitative, real time PCR using a protocol developed in our previous study (Kulshreshtha et al, 2014). Additionally, DNA samples were sent for next generation sequencing analysis to McGill University and Genome Quebec Innovation Centre, Montreal, Quebec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little literature on incorporating seaweeds as a protein source into the diets of poultry and swine. In contrast, there are many studies examining the functional effects of seaweed and their extracts on immune function, gut health, and meat and egg quality (Katayama et al, 2011;Kulshreshtha et al, 2014;Michalak et al, 2011;Walsh, Sweeney, O'Shea, Doyle, & O 'Doherty, 2013). However, these studies use low inclusion levels (<5%) that contribute little protein to the diet or, its corollary, that the seaweeds do not displace traditional protein sources in the feed.…”
Section: The Use Of Whole Seaweeds In Mono-gastric Livestock Dietsmentioning
confidence: 99%
“…They improve the growth of beneficial bacteria in the environment of harmful microbiota. MAAs is unique components of red seaweeds and seaweed components are known as supportive reinforcement of the microbiota in intestinal diseases [17][18][19][20]. MAAs had been shown to regulate intestinal epithelial cell differentiation and cytokine (IL-1β, IL-6) production [21].…”
Section: Mycosporin-like Amino Acidsmentioning
confidence: 99%